Optimalisasi Penugasan Kerja Perawat di Poliklinik Rumah Sakit Pekanbaru Medical Centre Tahun 2024 - Anggy Vidian; Hetty Ismainar; Awaliyah Ulfah (Syntax Corporation Indonesia, 2025)
Optimal work assignment is one of the keys in improving the quality of services in hospitals, especially in polyclinics which are often the main door to health services. This study aims to analyze and optimize the work assignment of nurses at the Pekanbaru Medical Centre Hospital Polyclinic in 2024. With a quantitative descriptive approach, data was collected through direct observation, interviews with nurses, and workload analysis using the Workload Indicator of Staffing Need (WISN) method. The results of the study showed that there was an imbalance in the workload between nurses which had an impact on service efficiency and patient satisfaction levels. Optimization is carried out by implementing workload redistribution based on the analysis of the needs of nurses, nurses, and polyclinic operating hours. The implementation of this strategy has succeeded in increasing work efficiency by 15% and patient satisfaction has increased by up to 20% compared to the previous year. This study provides practical recommendations for hospital management to improve nurse performance and service quality in a sustainable manner.